Wolbachia strain w AlbB shows favourable characteristics for dengue control use in Aedes aegypti from Burkina Faso - (:unkn) unknown (My University, 2024)
Dengue represents an increasing public health burden worldwide. In Africa, underreporting and misdiagnosis often mask its true epidemiology, and dengue is likely to be both more widespread than reported data suggest and increasing in incidence and distribution. Wolbachia ‐based dengue control is underway in Asia and the Americas but has not to date been deployed in Africa. Due to the genetic heterogeneity of African Aedes aegypti populations and the complexity of the host‐symbiont interactions, characterization of key parameters of Wolbachia ‐carrying mosquitoes is paramount for determining the potential of the system as a control tool for dengue in Africa. The w AlbB Wolbachia strain was stably introduced into an African Ae. aegypti population by introgression, and showed high intracellular density in whole bodies and different mosquito tissues; high intracellular density was also maintained following larval rearing at high temperatures. No effect on the adult lifespan induced by Wolbachia presence was detected. Moreover, the ability of this strain to strongly inhibit DENV‐2 dissemination and transmission in the host was also demonstrated in the African background. Our findings suggest the potential of harnessing Wolbachia for dengue control for African populations of Ae. aegypti.
Keywords: African Research